The Adaptation of Indoor Health and Comfort Criteria to Mitigate Covid-19 Transmission in the Workplace - Wardhani, Dyah Kusuma; Susan, Susan (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research discussed the application of indoor health and comfort criteria that needed to be reviewed to create good indoor environmental quality and reduce the transmission of the Covid-19 virus where people spent most of their time indoors. A confined area, which was poorly ventilated and reliant on air conditioning, helped transmit the Covid-19 virus easily as air recirculation was the main cause of office clusters. One of the categories of Greenship Interior Space, Indoor Health and Comfort (IHC), could be used as a guide for creating better indoor quality. The method used for the research was a systematic literature review to define, study, analyze, and classify all available research relating to adaptation of indoor health and comfort criteria to mitigate the transmission in the workplace. The results show the adjustment to IHC criteria in IHC 1-10, which focus on providing good air quality by introducing outside air, stopping air recirculation, reducing indoor user capacity, and reducing indoor biological and chemical pollutants. To illustrate the implementation of the new normal, Ciputra University workplace was being observed, as the findings of the results, some strategies that are in line with the objectives of IHC 1, IHC 2, and IHC 5. Adjustment of these criteria must be supported by implementing health protocols through basic hygiene routines, fitness screening, and maintaining physical distancing.